STRIP ROLLING MILL’S FLEXIBLE MULTI-BODY SYSTEM COUPLING DYNAMIC MODELING RESEARCH - ZHANG Yang; SUN JianLiang; DU DongYuan (Jixie qiangdu)
During the rolling process, the rolling mill’s working stability is determined by the system’s dynamic characteristics. Among which, the roll system’s rigid motion and the work roll and backup roll‘s flexural deformation movement are the main factors that affect both the steel strip’s thickness precision and surface quality. Especially for the heavy plate four-high mill system, the work roll’s flexural deformation movement significantly affects the shape control of steel strip due to its direct contact with the stock. The influence of the dynamic properties of rolling mill system’s rigid vibration on work roll and backup roll’s flexural deformation movement was investigated in this paper. Furthermore, a rigid flexible coupling dynamic model of the strip rolling mill is established. Consequently, the difference between the natural mode shape function of the roll derived by the traditional structural dynamics and the mode shape function deduced with the influence of rolling mill’s rigid vibration has been analyzed in different moments.